Attitude and Practice of Universal Healthcare Precautions (UHPs) among Healthcare Workers in Healthcare facilities of Jaipur, Rajasthan - Jain, Anjali; Singh, Sejal; Hussain, Suhana; Jain, Ashish; Vyas, Nitya; Fatima, Anum (Indian Journal of Community Health, 2024)
Background: Healthcare workers are more prone to occupational illness due to catching infections as they are involved in practices, if they lack the adequate knowledge and attitude to practice and comply with the UHPs Objective:- assess the knowledge, attitude and practice of UHPs among the healthcare workers Method:- descriptive cross-sectional study was conducted on healthcare workers including doctors, nurses, pharmacists, internees (both medical and nursing) laboratory technicians including intensive care unit (ICU) technicians, X-ray technicians, etc.. A pretested and predesigned questionnaire was used on 240 participants. Knowledge questionnaire in a true false statement based format; In attitude questionnaire responses were plotted on a 3-point scale i.e. “agree”, “neutral”, and “disagree”; Practice questionnaire was an observation questionnaire filled by us directly. All the results were transferred onto Microsoft excel sheet and evaluated statistically. Results majority 89.16% knew UHPs should be followed by all persons irrespective of their diagnosis and 77.92% were aware that all body fluids are considered infectious. Majority i.e. 91.25% agreed that UHPs are effective. There was a mixed response when asked if they perceived their own risk of HIV/HCV high, 76.25% agreed, 6.67% disagreed while 17.08% were neutral. 74.16% agreed that all body fluids are infectious. We observed 94.58% always while 5% sometimes wore gloves. 21.67% never changed gloves between patients. Recapping of used needles was never done by 55%. Conclusion: UHPs are the keystones for infection control and only complete adherence to them in form of good practice can reduce the risk of transmission of diseases. Major barrier to compliance with UHPs were identified to be shortage of time, heavy workload, non availability of PPEs, discomfort in their use and negligence due to lack of knowledge.